Effects of a Combination of Essential Oils (Victus LIV), Increased Zinc Oxide and Copper Sulfate, or Their Combination in Nursery Diets on Pig Performance - A. Langemeier; J. Morton; S. Scotten; M. T. Thayer; J. L. Nelssen (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 280 weaned pigs (Line 600 × 241; DNA, Columbus, NE; initially 11.4 lb) were used in a 35-d study to compare the effects of feeding growth promoting alternatives (added trace minerals, copper and zinc, or essential oils (Victus LIV; DSM Nutritional Products, Parsippany, NJ), alone or in combination, on nursery pig performance in comparison to Carbadox, (Mecadox, Phibro Animal Health, Teaneck, NJ). Pigs were allotted to 1 of 7 dietary treatments in pens of 5 at weaning in a randomized complete block design with 8 replications per treatment. Dietary treatments were arranged with a negative control diet with no growth promoting feed additive, a positive control with added carbadox or 5 treatments including added copper (Cu) sulfate (CuSO4; 0 vs. 125 ppm Cu) and added zinc (Zn) oxide (ZnO; 0 vs. 3,000 ppm Zn from d 0 to 7 and 2,000 ppm Zn from d 7 to 35), essential oils from Victus LIV at either 0.29 lb/ton (145 ppm) or 0.86 lb/ton (435 ppm). These supplements were fed alone or in combination. From d 0 to 35 experimental diets were fed in a meal form. Feeding carbadox, essential oil at 145 ppm or added trace minerals (Cu and Zn) improved ADG (P<0.05) of nursery pigs compared to the negative control diet. The use of added Cu and Zn or 145 ppm of Victus LIV alone or in combination sustained ADG and F/G that was competitive with pigs fed carbadox. In summary, under the conditions of this experiment, pigs fed the combination of zinc and copper or 145 ppm Victus LIV had growth performance similar to those fed carbadox (P>0.05).
Keywords: alternative; carbadox; copper; essential oil; nursery pig; added trace minerals; zinc